Bringing Together Multiple and Diverse Forms of Resistance to Innovation: A Rhetorical Approach to the Anti-5G Movement - Louis Vuarin; David Massé (M@n@gement)
Numerous resistance or contestation movements exhibit a surprising ability to bring together individuals with very different sensibilities and arguments that may be contradictory. Rooted in a study of a resistance movement against 5G technology, this article helps to better understand the phenomenon whereby multiple and heterogeneous resistances come together within the same movement by showing the role played by rhetoric. We analyse the great diversity of arguments in 5G resistance, focussing on four main lines that structure the arguments, and we shed light on an ‘argument decentring’ phenomenon where, although they may not adopt the arguments advanced by other opponents, some actors leverage the resulting controversy to legitimate their own discourse and increase the credibility of their own lines of argumentation. By considering rhetoric as a mechanism that aggregates resistance movements, this study contributes to a better understanding of the mechanisms and effects of argument heterogeneity, in particular online or on social media.